ANALISIS FAKTOR PENGHAMBAT IMPLEMENTASI K-13 DAN STRATEGI MENGATASI HAMBATAN K-13 PADA PEMBELAJARAN KIMIA DI SMKN 1 TELUK KUANTAN - Nofri Yuhelman; Rosa Murwindra; Dwi Putri Musdansi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
ABSTRACTThis study aims to determine the factors inhibiting the implementation of the 2013 curriculum, and to know what efforts in overcoming obstacles implementation of the 2013 curriculum.This research is a type of qualitative research with descriptive approach that takes the background of SMKN 1 Teluk Kuantan. Sampling refers to the technique of Purposive sampling with Respondents consisting of Chemistry Teachers, the representative curriculum. Curriculum and students of class X. Data collection is done by conducting interviews, participant observation, documentation and questionnaire. Data analysis is done by choosing, simplifying and transforming rough data that emerges from the written records in the field, so that it becomes more focused in accordance with the object of research. After the data analysis done then draw conclusions. Data validity is done by triangulation method with triangulation model of source and triangulation technique.The results show that the barriers that occur is the determination of KBM is sometimes difficult due to lack of labor and the lack of student interest makes it difficult to develop teaching materials oriented student center. Efforts to overcome this is the need for the availability of facilities and infrastructure such as the completeness of tools and practical materials and the addition of training curriculum 2013 in order to develop teaching materials oriented student center. Implementation of the 2013 curriculum in the implementation of learning, teachers have run the 2013 curriculum although sometimes do not adjust to the syllabus and RPP. Obstacles that occur is the method of learning approaches such as PBL, PBL is still difficult to implement because students have less literature and experience. Efforts are made teachers do various methods approach to create an active learning atmosphere and not saturate for learners, so they are more active in digging information. Implementation of the 2013 curriculum in the evaluation system, evaluation techniques used are formative and summative tests. The hindrance that occurs is that psychomotor assessment is rather difficult to do because there is rarely any practice in KBM. Efforts are made teachers classify learners in learning activities, assisted by individual assessments between friends, collaboration assessment with other teachers and the addition of tasks. Keywords: Obstacles K-13, Chemistry Learning, K-13 Implementation